Peningkatan Partisipasi Kunjungan Posyandu melalui Gerakan Posyandu Sehat dan Aktif (GPSAKTI) pada Posyandu Warga Sehati Puskesmas Wonorejo Samarinda - Istiqomah Nur Oktavia; Lia Kurniasari; Nur Jannah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Posyandu (Integrated Health Service Post) is a community-based initiative designed to provide basic health services, particularly for mothers and children. However, low attendance remains a challenge at Posyandu Warga Sehati in Karang Anyar. This community engagement program aimed to increase attendance through the